COCOA SEED GROWTH RESPONSE (THEOBROMA CACAO L.) IN NURSERIES DUE TO MULCH GIVING AND SOME WATERING INTERVALS - Efi Said Ali; Asmara Sari (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
Cocoa plant (Theobroma cacao L.) is one of Indonesia's export commodities in addition to rubber, tea, palm oil and others. With proper and regular mulch giving cocoa plants will have better growing power (Umboh, 2010). According to Umboh, (2010) mulch is an attempt to provide nutrients into the soil so that the physical, chemical and biological conditions of the soil are in accordance with the demands of plants. So the purpose of mulching is to provide nutrients in the soil to get good growth and increase soil productivity. In addition, mulch can also reduce the evaporation of water above the surface of the soil. This study uses Random Group Design (RAK), 3 repeats and the number of plots 12 plots per repeat, so that the total number of plots is 36 plots, while the factor to be tested consists of 2 factors: The first factor is the administration of mulch (B) consisting of 3 levels, namely, Mulch Factor B0, Without mulch, B1 rice husk mulch, B2 Mulch cane pulp While the second factor of water administration (W), water is given according to airy capacity (500 ml per polybag), consists of 4 levels, namely: Water Giving: W1 :1 day twice (1x2), W2 :1 day once (1x1), W3 : 2 days once (2x1) W4 :3 days (3x1) From the results of the study obtained results that the provision of mulch gives a real influence on the number of strands of leaves at the age of 9 weeks after planting and an unreal effect on plant height, leaf area, wet weight of roots and dry weight of roots. Watering treatment exerts an unreal influence on all observed parameters. While the interaction between mulch administration (B) and watering (W) exerts an unreal influence on all observed parameters.